2011
DOI: 10.1111/j.1399-6576.2011.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist vs. pressure support ventilation in critically ill patients: an observational study

Abstract: The ventilator mode NAVA seems to be well tolerated in a heterogeneous group of critically ill patients. Pre-setting of the NAVA level during PSV can result in an overestimation of the required ventilator support. An additional titration of the NAVA level ads valuable information although difficult to interpret in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…15 Several patient studies demonstrated plateaus in Vt, Pvent, or transpulmonary pressure during increasing NAVA levels associated with EAdi suppression. 7,9,10,16,17,33,34 Our observation of a more favourable distribution of aeration with less atelectatic regions after ALI compared to normal lungs (i.e. HCL induced lung injury improved pattern of lung aeration in cNAVA ventilated rabbits) agree with findings that HCL-induced ALI induces heterogeneous injury and de-recruitment of the lungs.…”
Section: Protection From Lung Over-distensionsupporting
confidence: 87%
“…15 Several patient studies demonstrated plateaus in Vt, Pvent, or transpulmonary pressure during increasing NAVA levels associated with EAdi suppression. 7,9,10,16,17,33,34 Our observation of a more favourable distribution of aeration with less atelectatic regions after ALI compared to normal lungs (i.e. HCL induced lung injury improved pattern of lung aeration in cNAVA ventilated rabbits) agree with findings that HCL-induced ALI induces heterogeneous injury and de-recruitment of the lungs.…”
Section: Protection From Lung Over-distensionsupporting
confidence: 87%
“…During a recent observational study, transferring patients to NAVA was uneventful and the NAVA level contributed to adjustments of the preset NAVA level [80]. Interpretation of several interacting physiological parameters might be difficult in cases in which there is no marked decrease in EAdi during NAVA titration [80]. An automated approach enabled faster identification of the best NAVA level with a good accuracy [81].…”
Section: How Can the Optimal Nava Level Be Determined?mentioning
confidence: 99%
“…12,17 However, reported experience with NAVA is limited to small case study which emphasizes brief physiologic trials. 31,[49][50][51][52][53][54] Finally, any patient requiring substantial sedation or having hemodynamic compromise would not be appropriate for PAV or NAVA. 55 …”
Section: Assisted Ventilation: Conclusionmentioning
confidence: 99%